Digital Future Classroom: the physical space and the inclusion of the NEET/Refugee population: conceptual and theoretical frameworks and methodology - Sardinha, Lara
The classroom is one of the privileged environments aiming knowledge construction and the establishment of social relationships as well as of cultural exchanges. Studies regarding classroom environment, focusing the pedagogical approaches, are countless; however, studies regarding the classroom environment as the physical space are significantly fewer. Nevertheless, a new classroom physical space – the Future Classroom Lab (FCL) - has been developed based, in part, on 21st Century Skills. Spaces like the FCL are spreading throughout Europe, existing already more than 2,600 FCL’s. The Information and Communications Technology (ICT) advent and the ICT-based emergent pedagogical approaches contributed to the increase of studies concerning the physical classroom environment, as the classroom space and layout became no longer the most suitable. But are these new spaces suitable for the Non in Education, Employment or Training (NEET)/Refugee population and are they being designed and conceived to promote the inclusion of these populations? Considering this scenario and the NEET and Refugee populations’ current crisis in the European Union [1], [2]) the research that this paper presents aims to investigate innovative interior design strategies to the classroom architectural space in order to promote the inclusion of these specific populations: through the analysis of how the FCL spaces are being used in the European Schoolnet FCL network and through the observation of some of these spaces in Portugal, a Digital Future Classroom (DFC) is going to be designed. Privileging the enabling spaces approach [3] on the classroom complexity spaces (architectural, social, cognitive, emotional, epistemological, cultural and organizational, technological and the virtual space), this ongoing research aims at understanding how to “translate” these concepts into the classroom interior design, aiming the promotion of the user’s inclusion. This analysis also gathers the spatial and pedagogical semiotics as well as the spatial pedagogy inherent to the classroom. This article presents the relevance of the research supported by its theoretical and conceptual frameworks and the methodology that is being adopted. The present research, mainly qualitative, can be considered under the constructivist (or socio-constructivist) paradigm and with a slight nuance of the critical theory paradigm. Considering also that “The researcher-as-bricoleur-theorist works between and within competing and overlapping perspectives and paradigms” [4, p. 5] the research design resorts to triangulation, as it uses “different methods in an attempt to confirm, cross-validate, or corroborate findings” [5, p. 24] in order to respond to each of the set objectives fulfilling all the requests.